Comparison of carbon balance and climate change mitigation potential of forest management strategies in the boreal forest of Quebec (Canada). (4th March 2019) - Paradis, Laurence; Thiffault, Evelyne; Achim, Alexis
Abstract: Management of the world's forests can play a role for climate change mitigation by increasing CO2 storage in vegetation biomass and harvested wood products, and by displacing CO2 -intensive materials such as steel or concrete. This study aimed to determine how management of boreal forest stands could contribute to climate change mitigation in the context of ecosystem-based management. The study was based on the comparison of different strategies applied to a balsam fir-white birch stand in the Eastern boreal forest of Quebec (Canada). Five scenarios were simulated over a 199-year period at the stand level: a reference scenario involving clearcut at 50-year intervals, and four alternative scenarios clearcut with longer rotation length (70 and 80 years), partial cut, and a no harvest scenario. The study included an appropriate sensitivity analysis of the results. Overall, scenarios with longer clearcut rotations and, to a lesser extent, partial cut resulted in a higher potential to mitigate climate change. The substitution effect of wood products was revealed as a key aspect, suggesting that wood product manufacturing and utilization on the markets, and not only forest management, need to be carefully considered.